2012
DOI: 10.12677/bp.2012.21006
|View full text |Cite
|
Sign up to set email alerts
|

The Affect of Growth and Phenol Degrading on Phenol Degrading Strain XH-10 with Different Metal Ions

Abstract: This article surveyed the influence which 18 metal ions on phenol degrading bacterium XH-10 growth and the phenol degradation. , Mn 2+ at lower concentration to the phenol degrading bacterium XH-10 growth have promoter action, degrades the inhibitory action to be small, at high concentrations to the bacterium growth and the phenol degradation have obvious inhibitory; Ba 2+ the inhibitory action which degrades to the phenol is obvious, but at lower concentration have promoter action to the phenol degrading bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Unlike the special requirements for expression of PhcMnp, the expression of ZHD101.1 was theoretically not affected by Mn 2+ and hemin. However, high concentrations of Mn 2+ also affects the enzyme expression by inhibiting the growth of yeast cells (Tang et al 2012 ), so the enzyme activities of ZHD101.1 also showed decreasing trends with the increasing concentrations of Mn 2+ added (Fig. 3 d, e).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Unlike the special requirements for expression of PhcMnp, the expression of ZHD101.1 was theoretically not affected by Mn 2+ and hemin. However, high concentrations of Mn 2+ also affects the enzyme expression by inhibiting the growth of yeast cells (Tang et al 2012 ), so the enzyme activities of ZHD101.1 also showed decreasing trends with the increasing concentrations of Mn 2+ added (Fig. 3 d, e).…”
Section: Resultsmentioning
confidence: 91%
“…It was reported that enzyme PhcMnp was regulated by Mn 2+ at the transcriptional level, and a certain amount of Mn 2+ may promote the synthesis of PhcMnp (Wang 2014 ; Whitwam and Tien 1996 ). However, when the concentration of Mn 2+ was too high, it inhibited the enzyme expression (Tang et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%